Keabsahan Akta Notaris terkait Risalah Rapat Umum Pemegang Saham Perseroan Terbatas yang Dilakukan Secara Online - I Made Pradnyana Utama (Jurnal Hukum Lex Generalis, 2025)
This article was written with the aim of reviewing and analyzing the validity of notarial deeds related to minutes of general meetings of shareholders of limited liability companies conducted online. The research method used is normative legal research because the focus of the study is based on the conflict of norms between "Article 16 paragraph (1) letter m of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary with Article 90 paragraphs (1) and (2) of Law Number 40 of 2007 concerning Limited Liability Companies regarding the validity of the deed of minutes of the general meeting of interns of a limited liability company carried out online based on the qualifications of authentic deeds and the authority of the notary. The results of the discussion of this paper are first, the validity of the deed of minutes of the general meeting of shareholders carried out online is not valid as an authentic deed but only as a private letter. This is because the authority of the Notary in making authentic deeds must be in accordance with the provisions of the Civil Code and also the Law on the Position of Notary where the deed of minutes of the GMS made on the basis of online/electronic media has violated the obligations and authority of the Notary. Second, the notary's responsibility is limited to the accuracy of the date, The time and place where the deed was made, related to the substance of the deed made by the notary regarding the implementation of the online GMS, is the client's responsibility.